Differential effects of low dose lidocaine on C-fiber classes in humans - Bergemann, Jennifer; Obreja, Otilia; Schmelz, Martin (The journal of pain, 2012)
The nonselective sodium channel blocker lidocaine is widely used as a local anesthetic but also systemically for treatment of postoperative and neuropathic pain. Voltage-gated sodium channels are crucial for action potential generation and conduction, and their availability controls the amount of activity-dependent conduction velocity slowing. This important axonal property, as assessed by microneurography, is used to differentiate human mechanoinsensitive (silent) nociceptors from the classical polymodal nociceptors. In the current study, microneurography was used to assess axonal properties of the 2 main nociceptor classes in humans, before and after intradermal injection of lidocaine .1% or control saline solution in the receptive field. In mechanosensitive nociceptors, lidocaine reduced baseline conduction velocity and turned activity-dependent slowing into speeding of conduction. In contrast, mechanoinsensitive fibers were not affected in their baseline conduction velocity or their activity-dependent slowing, but probability of conduction block with repetitive stimulation increased. Recovery cycles showed reduced hyperpolarization in all C-fiber classes after lidocaine injections. These results support our hypothesis that sodium channel subtypes are differentially expressed in the 2 nociceptor classes of mechanosensitive C-fibers (CMs) and mechanoinsensitive C-fibers (CMis). Perspective This study reveals that microneurography can be used to assess pharmacological effects on single C-fibers directly in humans.
Available online 24 November 2012
Gesehen am 21.06.2018